1995
DOI: 10.1128/jb.177.20.5878-5883.1995
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis amino acid deaminase: cloning, nucleotide sequence, and characterization of aad

Abstract: Proteus, Providencia, and Morganella species produce deaminases that generate ␣-keto acids from amino acids. The ␣-keto acid products are detected by the formation of colored iron complexes, raising the possibility that the enzyme functions to secure iron for these species, which do not produce traditional siderophores. A gene encoding an amino acid deaminase of uropathogenic Proteus mirabilis was identified by screening a genomic library hosted in Escherichia coli DH5␣ for amino acid deaminase activity. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 42 publications
0
64
0
Order By: Relevance
“…Lower identities (14.9, 14.6, and 12.3%) were found with the ␤-subunit of the heterotetrameric sarcosine oxidase from Corynebacterium sp. P-1 (49), with the N terminus of dimethylglycine dehydrogenase from rat liver (50), and with the amino acid deaminase from Proteus mirabilis (51). High identities occurred with a not yet identified gene product (accession number U23529) from Caenorhabditis elegans.…”
Section: Purification Of Sarcosinementioning
confidence: 98%
“…Lower identities (14.9, 14.6, and 12.3%) were found with the ␤-subunit of the heterotetrameric sarcosine oxidase from Corynebacterium sp. P-1 (49), with the N terminus of dimethylglycine dehydrogenase from rat liver (50), and with the amino acid deaminase from Proteus mirabilis (51). High identities occurred with a not yet identified gene product (accession number U23529) from Caenorhabditis elegans.…”
Section: Purification Of Sarcosinementioning
confidence: 98%
“…They are also produced by transaminases and deaminases and in other metabolic processes. In species such as P. mirabilis (21), degradation of amino acids is due to specific amino acid deaminases; indeed, the production of ␤-phenylpyruvic acid by the action of phenylalanine deaminase, detectable as a colored ferric complex, is a key diagnostic tool for the Proteus-Providencia-Morganella group (15). Salmonella, however, is phenylalanine deaminase negative, producing only trace amounts of ␤-phenylpyruvic acid and other amino acid degradation products primarily by aminotransferase-catalyzed removal of amino groups to KGA.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that amino acid deaminase (Aad) produces α-keto acids which serves as siderophores involved in iron acquisition (DRECHSEL et al 1993, MASSAD et al 1995. Recently, HIMPSI et al (2010) described proteobactin and yersiniabactin related siderophore function in P. mirabilis.…”
Section: Pathogenicitymentioning
confidence: 99%